Editing ourselves, naming ourselves: enunciation and subjects of the Taller Colectivo de Edición (Collective Edition Workshop) - Rubin, María José (2021)
The Collective Edition Workshop (Taller Colectivo de Edición, TCE) is an extracurricular course that integrates the Prison Extension Program of the Faculty of Philosophy and Literature at the University of Buenos Aires (UBA). It is taught in university centers of the UBA 23rd program, where it displays a collective work of reflection and action around the meanings built as part of the editorial task and with the horizon of publication of a journal. We propose reading texts that address the names of journals to question and re-signify these names, discussing meanings rooted in discourses that relate to confinement and characterize people deprived of their freedom from a punitive and stigmatizing perspective. Reviewing the own name as an editing collective condenses our working logic, understanding that editing in this context involves an enunciative position that goes beyond the workshop’s framework and implies movement in subjective terms.